Analysis of Investor Reactions to the Launch of Super Holding Danantara: Event Study on Shares of Danantara Member State-Owned Enterprises - Fadila, Nuriya; Kusniawati, Kusniawati; Sarah, Sriwahyuni; Habbe, Abdul Hamid; Bandang, Agus (Dinasti International Journal of Digital Business Management, 2025)
This study analyzes the capital market reaction to the announcement of the formation of the Danantara Investment Management Agency (BPI) on February 24, 2025. Using an event study method with an 11-day observation window (t-5 to t+5) on the shares of 11 Danantara-member state-owned enterprises (SOEs), the study found a negative market response. This was evidenced by a consistent decline in Cumulative Average Abnormal Return (CAAR) to -5.63%, indicating short-term wealth destruction. Although a paired sample t-test showed no significant difference between abnormal returns before and after the event, the persistent downward price trend indicates pre-announcement information leakage and high investor skepticism regarding the governance risks of the new SOE structure